What twitter can tell us about the stock market - Hazem, Sama-Mohamed; Mohamed, Ehab K.A.; Ali, Heba (ANDULI, Revista Andaluza de Ciencias Sociales, 2019)
The announcement of a certain event taking place may be important and impactful with regard to the stock market and share prices, even more than the effectiveness and significance of the event itself. The aim of this study is to analyze the effect of financial event announcements via social media, specifically Twitter, on share returns of stocks on the Financial Times Stock Exchange 100 Index. Our research questions were tested on a sample of 833 event observations retrieved from official Twitter accounts for two years (1 January 2014 - 16 February 2016).  The test was concerned with tracking stock return behavior on the event day (day 0), the pre-event window and the post-event window using the event-study methodology. This study found that there is a significant relationship between share prices and the events announced via Twitter, the type of tweets, news categories and tweeting intensity of the company involved. Classifying based on the industry of the announcing company had no significant relationship to stock return behavior.